Validity of the Utrecht scale for evaluation of rehabilitation-participation restrictions scale in a hospital-based stroke population 3 months after stroke. Issue 7 (3rd October 2022) - de Graaf, Joris A.; Volkers, Eline J.; Schepers, Vera P.M.; Visser-Meily, Johanna M.A.; Post, Marcel W.M.
ABSTRACT: Background: The Utrecht Scale for Evaluation of Rehabilitation-Participation Restrictions scale (USER- P -R) is a promising patient-reported outcome measure, but has currently not been validated in a hospital-based stroke population. Objective: To examine psychometric properties of the USER- P -R in a hospital-based stroke population 3 months after stroke onset. Methods: Cross-sectional study including 359 individuals with stroke recruited through 6 Dutch hospitals. The USER- P -R, EuroQol 5-dimensional 5-level questionnaire (EQ-5D-5 L), Patient Reported Outcomes Measurement Information System 10-Question Global Health Short Form (PROMIS-10), modified Rankin Scale (mRS) and two items on perceived decrease in health and activities post-stroke were administered in a telephone interview 3 months after stroke. The internal consistency, distribution, floor/ceiling effects, convergent validity and discriminant ability of the USER- P -R were calculated. Results: Of all participants, 96.9% were living at home and 50.9% experienced no or minimal disabilities (mRS 0–1). The USER- P -R showed high internal consistency (α = 0.90) and a non-normal left-skewed distribution with a ceiling effect (21.4% maximum scores). A substantial proportion of participants with minimal disabilities (mRS 1) experienced restrictions on USER- P -R items (range 11.9–48.5%). The USER- P -R correlated strongly with the EQ-5D-5 L, PROMIS-10 and mRS. The USER- P -R showed excellent discriminant ability in more severely affected individuals with stroke, whereas its discriminant ability in less affected individuals was moderate. Conclusions: The USER- P -R shows good measurement properties and provides additional patient-reported information, proving its usefulness as an instrument to evaluate participation after 3 months in a hospital-based stroke population.